Living with dementia in hospital wards: a comparative study of staff perceptions of practice and observed patient experience. (20th January 2016) - Innes, Anthea; Kelly, Fiona; Scerri, Charles; Abela, Stephen
Abstract : Aims and objectives: To ascertain the experiences, attitudes and knowledge of staff working in two Maltese hospital wards and the observed experiences of people with dementia living there. To examine the impact of recommendations made in October 2011 for improving the psychosocial and physical environments of the wards 1 year later. Background: There is an increasing policy recognition of the need for a better trained and educated dementia care workforce and of ensuring that the environmental design of care settings meets the needs of people with dementia. Design and methods: At both time points, three established and validated data‐collection methods evaluated (i) staff/patient interaction and patient experience, (ii) the extent to which the wards met dementia friendly principles and (iii) staff views about their work environment and their perceptions about their practice. Sixteen (five male and 11 female) patients with dementia and 69 staff in the two wards participated in the study. Results: We noted small but important changes; however, the physical and psychosocial environments of the wards did not always align to current recommendations for dementia care, with staff perceptions of care delivery not always reflecting the observed experiences of care of those living with dementia. Conclusions: Comparing staff questionnaire data with observational methods offered a unique opportunity to understand multiple perspectives in a complex hospital setting. Incorporating these perspectives into staff and management feedback allowed for recommendations that recognised both patient‐centred values and staff constraints.